In the name of socialism, in the shadow of the monarchy post-war monument care in Central Europe - Bachtík, Jakub 1985-; Johanidesová, Tereza; Uhlíková, Kristina 1974- (Artefactum, 2022)
This English-language publication explores approaches to architectural and urban heritage, the development of heritage conservation, and its most prominent topics in post-1945 Central Europe, a territory where conservators’ and historians’ perspectives collided in the face of turbulent political and social change. The book is a follow-up to a conference on the same topic held in 2021. It outlines our current state of knowledge, presenting broadly conceived contributions and detailed explorations of particular themes through individual heritage monuments and case studies.
Keywords: Geschichte 1945-2022; Denkmalpflege; Sozialistische Staaten; Ostmitteleuropa; Aufsatzsammlung